Acetylcholinesterase (AChE) is an important link in the apoptotic pathway induced by hyperglycemia in Y79 retinoblastoma cell line - Shehadeh Mashour, Raneen; Heinrich, Ronit; Garzozi, Hanna J; Perlman, Ido (Frontiers in Molecular Neuroscience, 2012)
Acetylcholinesterase (AChE) expression was found to be induced in the mammalian CNS, including the retina, by different types of stress leading to cellular apoptosis. Here, we tested possible involvement of AChE in hyperglycemia-induced apoptosis in a retinal cell line. Y79 retinoblastoma cells were incubated in starvation media (1% FBS and 1mg/ml glucose) for 16-24 hours, and then exposed to hyperglycemic environment by raising extracellular glucose concentrations to a final level of 3.5mg/ml or 6mg/ml. Similar levels of mannitol were used as control for hyperosmolarity. Cells were harvested at different time intervals for analysis of apoptosis and AChE protein expression. Apoptosis was detected by the cleavage of Poly ADP- ribose polymerase (PARP) using western blot, and by Terminal Deoxynucleotidyl–transferase-mediated dUTP nick-end-labeling (TUNEL) assay. AChE protein expression and activity was detected by western blot and by the Karnovsky and Roots method, respectively. MissionTM shRNA for AChE was used to inhibit AChE protein expression. Treating Y79 cells with 3.5mg/ml of glucose, but not with 3.5mg/ml mannitol, induced apoptosis which was confirmed by TUNEL assay and by cleavage of PARP. A part of the signaling pathway accompanying the apoptotic process involved up-regulation of the AChE-R variant and an N-extended AChE variant as verified at the mRNA and protein level. Inhibition of AChE protein expression by shRNA protected Y79 cell from entering the apoptotic pathway. Our data suggest that expression of an N-extended AChE variant, most probably an R isoform, is involved in the apoptotic pathway caused by hyperglycemia in Y79 cells.